PROBLEMATIKA KONSINYASI SEBAGAI MEKANISME DALAM PENGADAAN TANAH UNTUK KEPENTINGAN UMUM (Studi Kasus Pembangunan Jalan Tol Solo-Mantingan) - Fitra Restu Suryaningrum; Mochamad Najib Imanullah (Fakultas Hukum Universitas Sebelas Maret, 2023)
Abstract This article departs from the many problems that occur in the process of land procurement which as a means to obtain land for development with the aim of public interest. The public interest must include the interests of the majority of the community including the interests of landowners whose land is affected by land procurement, so that the interests of the parties in this case the government as the party who will use the land can be fulfilled. The author uses a type of empirical legal research that is descriptive and with the type of primary data. With the technique of collecting literature and interview study data and using qualitative analysis techniques. The author then tries to analyze the consignment as a mechanism for land procurement for public interest development. In the process of land procurement, it must be carried out by consultation to determine the form and amount of compensation. Deliberation to determine the compensation is carried out no later than 120 (one hundred twenty) days, if within that period no agreement is reached regarding the form and amount of the compensation while the project in the public interest cannot be moved to another place, a deposit of compensation (consignment) is conducted at the district court in the territory the location of the land. Consignment in civil law is carried out if the creditor rejects the offer of payment from the debtor. The application of consignment in the procurement of land for the implementation of development in the public interest can be carried out for three reasons, namely first, development activities in the public interest that cannot be moved technically to another location; secondly, the deliberation had been going on for 120 days but did not reach an agreement; third, if there is a dispute over ownership after the determination of compensation. Consignment is a solution to the resolution of land procurement problems that help facilitate development in the public interest. Keywords: Public interest; consignment; land procurement; development AbstrakArtikel ini berangkat dari banyaknya permasalahan yang terjadi dalam proses pengadaan tanah yang mana sebagai sarana untuk memperoleh tanah yang akan dilakukan pembangunan dengan tujuan untuk kepentingan umum. Kepentingan umum harus mencakup kepentingan sebagian besar masyarakat termasuk kepentingan para pemilik tanah yang tanahnya terkena pengadaan tanah, sehingga kepentingan para pihak dalam hal ini pemerintah sebagai pihak yang akan menggunakan tanah dapat terpenuhi. Penulis menggunakan jenis penelitian hukum empiris yang bersifat deskriptif dan dengan jenis data primer. Dengan teknik pengumpulan data studi kepustakaan dan wawancara serta menggunakan teknik analisis kualitatif. Penulis selanjutnya berusaha untuk menganalisa konsinyasi sebagai mekanisme pengadaan tanah untuk pembangunan kepentingan umum. Dalam proses pengadaan tanah harus dilakukan dengan musyawarah untuk menentukan bentuk dan besarnya ganti rugi. Musyawarah untuk menentukan ganti rugi dilakukan paling lama 120 hari, jika dalam jangka waktu tersebut tidak tercapai kata sepakat mengenai bentuk dan besarnya ganti rugi sedangkan proyek untuk kepentingan umum tidak dapat dipindahkan ketempat lain, dilakukan penitipan uang ganti kerugian (konsinyasi) di pengadilan negeri yang mewilayahi letak tanah tersebut. Konsinyasi dalam hukum perdata dilakukan apabila kreditur menolak penawaran pembayaran dari debitur. Penerapan konsinyasi dalam pengadaan tanah bagi pelaksanaan pembangunan untuk kepentingan umum dapat dilakukan dengan tiga alasan, yaitu pertama, kegiatan pembangunan untuk kepentingan umum yang tidak dapat dipindahkan secara teknis ke lokasi lain; kedua, musyawarah telah berjalan selama 120 (seratus dua puluh) hari namun tidak mencapai kata sepakat; ketiga, apabila terjadi sengketa kepemilikan setelah penetapan ganti rugi. Konsinyasi merupakan sebuah solusi penyelesaian permasalahan pengadaan tanah yang membantu memperlancar pembangunan untuk kepentingan umum.Kata Kunci: Kepentingan umum; konsinyasi; pengadaan tanah; pembangunan